2010
DOI: 10.1088/0004-637x/721/1/323
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Black Hole X-Ray Source in an NGC 1399 Globular Cluster

Abstract: We have discovered an accreting black hole (BH) in a spectroscopically confirmed globular cluster (GC) in NGC 1399 through monitoring of its X-ray activity. The source, with a peak luminosity of L X ≃2×10 39 ergs s −1 , reveals an order of magnitude change in the count rate within ≃10 ks in a Chandra observation. The BH resides in a metal-rich [Fe/H]≃0.2 globular cluster. After RZ 2109 in NGC 4472 this is only the second black-hole X-ray source in a GC confirmed via rapid X-ray variability. Unlike RZ 2109, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…Such a change in absorption has also been reported from an extragalactic BH source, XMMU 122939.7+07533 (Maccarone et al 2007). This was at first attributed to a warping of the accretion disk (Shih et al 2010), but the presence of strong, broad O iii lines (Zepf et al 2008) suggests that a strong disk wind varies the amount of absorbing material along the line of sight.…”
Section: Spectral Fittingsupporting
confidence: 63%
“…Such a change in absorption has also been reported from an extragalactic BH source, XMMU 122939.7+07533 (Maccarone et al 2007). This was at first attributed to a warping of the accretion disk (Shih et al 2010), but the presence of strong, broad O iii lines (Zepf et al 2008) suggests that a strong disk wind varies the amount of absorbing material along the line of sight.…”
Section: Spectral Fittingsupporting
confidence: 63%
“…Observationally, the existence of accreting BHs in GCs has been supported by the detection of five luminous (above the NS Eddington limit), variable sources Brassington et al 2010;Shih et al 2010;Irwin et al 2010;Maccarone et al 2011). Using the TC/PTC criteria defined in this paper, four of these binary systems are persistent and could be ultracompact binaries with either a BH (Gnedin et al 2009) or NS with super-Eddington accretion and rather mild beaming (King 2011).…”
Section: Gc-lmxbsmentioning
confidence: 83%
“…There are 2 in NGC 1399 [432, 243, 313], and Paolillo et al [364] estimate that 65% of globular clusters in NGC 1399 host LMXBs. Brassington et al [60] have found 3 LMXBs in globular clusters associated with NGC 3379, of which 1 is a presumed black hole.…”
Section: Observationsmentioning
confidence: 99%